A treasury of the world's great letters from ancient days to our own time : containing the characteristic and crucial communications, and intimate exchanges and cycles of correspondence, of many of the outstanding figures of world history, and some notable contemporaries - Schuster, Max Lincoln (London Toronto : William Heinemann, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie